THE INFLUENCE OF WORK ETHIC, ORGANIZATIONAL COMMITMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE ON PT. KILANG LIMA GUNUNG PADANG - Permana, Redo Zulio; Dewi, Aminar Sutra (Bina Bangsa International Journal of Business and Management, 2022)
Human resources have a central role for the company in the process of realizing goals, so to make it happen it takes maximum effort from the company by improving all human resource capabilities within the company, because this is the main key for the company to improve the performance of its employees. This study aims to test effect of work ethic on employee performance, to test effect of commitment on employee performance, to test effect of work discipline on employee performance. The sampling of the research used saturated sampling as many as 96 samples, using multiple linear regression analysis. The results show that work ethic has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance